2017
DOI: 10.1007/s10973-017-6252-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyclodextrin complexation on solubility of novel anti-Alzheimer 1,2,4-thiadiazole derivative

Abstract: New 1,2,4-thiadiazole derivative displaying neuroprotective potential and high activity in the treatment of Alzheimer's disease has been synthesized. The objective of this study was to improve the aqueous solubility of this drug-like compound by means of complex formation with native and hydroxypropylated b-cyclodextrins. To this end, aqueous solubility of 1,2,4-thiadiazole derivative was investigated in the presence of b-cyclodextrins. It was shown that the phase solubility diagrams are of B s type demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Grinding of a drug/CD mixture often produces amorphous products [31,32,33,34,47,51,54,55,56,57,58,59,60,61,62,63,64,65] or products containing only traces of crystalline drug [33,37,53,66,67,68,69,70,71,72,73,74,75,76], depending on the time and intensity of grinding and on the physicochemical properties of both drug and CD subjected to grinding. Several authors have demonstrated, by the use of 13 C MAS CP/TOSS NMR spectroscopy, the actual inclusion complex formation in amorphous drug/CD products obtained by co-grinding; examples from the literature included two thiadiazole-based anti-Alzheimer drug candidates co-ground with βCD and HPβCD [27,37], a fentanyl/βCD [59], and a bisacodyl/βCD [54] co-ground system. However, even if the product contains a significant fraction of residual crystalline drug, it could be readily converted into inclusion complex upon dissolution in water, as demonstrated by Jablan et al [77].…”
Section: Mechanism Of the Inclusion Complex Formation In The Solidmentioning
confidence: 99%
See 3 more Smart Citations
“…Grinding of a drug/CD mixture often produces amorphous products [31,32,33,34,47,51,54,55,56,57,58,59,60,61,62,63,64,65] or products containing only traces of crystalline drug [33,37,53,66,67,68,69,70,71,72,73,74,75,76], depending on the time and intensity of grinding and on the physicochemical properties of both drug and CD subjected to grinding. Several authors have demonstrated, by the use of 13 C MAS CP/TOSS NMR spectroscopy, the actual inclusion complex formation in amorphous drug/CD products obtained by co-grinding; examples from the literature included two thiadiazole-based anti-Alzheimer drug candidates co-ground with βCD and HPβCD [27,37], a fentanyl/βCD [59], and a bisacodyl/βCD [54] co-ground system. However, even if the product contains a significant fraction of residual crystalline drug, it could be readily converted into inclusion complex upon dissolution in water, as demonstrated by Jablan et al [77].…”
Section: Mechanism Of the Inclusion Complex Formation In The Solidmentioning
confidence: 99%
“…Moreover, when compared to the complexes prepared by other techniques, amorphous products obtained by grinding in some cases presented superior solubility and dissolution properties, like that observed in case of co-ground products of oxaprozin with RAMEB, bile acids and chitosan [23] or with βCD or DIMEB [34], or of clonazepam with natural and derivative βCDs [32], or even of naproxen with acetylated CDs [64]. However, in other cases, complexes prepared by solvent based methods like coevaporation or freeze-drying showed superior dissolution properties and bioavailability [27,33,37,61,62,64,68,75]. Here, it must be taken into account that freeze-dried products, which often present superior performance over co-ground and coevaporated ones, have a highly porous structure that additionally contributes to the improvement in its dissolution rate and bioavailability [50,78].…”
Section: Mechanism Of the Inclusion Complex Formation In The Solidmentioning
confidence: 99%
See 2 more Smart Citations
“…CDs are recognized as effective excipients in the formulation of numerous drugs [ 7 10 ]. Upon grinding, CDs form inclusion complexes with the drugs in the solid state, resulting in a significantly faster dissolution rate and increased bioavailability [ 11 13 ]. In our previous studies, CDs acted either as reactants [ 14 15 ], or as additives [ 16 17 ], and were shown to display supramolecular interactions with the other reaction partners.…”
Section: Introductionmentioning
confidence: 99%